Impact of endometrial compaction on reproductive outcomes after cryotransfer of euploid embryos in a modified natural cycle: protocol for a prospective cohort study - De la Torre Perez, Esperanza; Carratalá-Munuera, Maria Concepción; Castillo-Farfán, Juan Carlos; Lledó-Bosch, Belén; Moliner-Renau, Belén; Bernabeu-García, Andrea; Bernabeu-Pérez, Rafael (Frontiers in Endocrinology, 2023)
Introduction. Embryo implantation is a complex and poorly understood process. Most studies to date have focused on the analysis of the endometrium at the end of the estrogenic phase, while the available data on its importance after secretory transformation are limited and inconsistent. Current evidence does not allow for a conclusive interpretation of the changes observed in the pre-implantation endometrium, whether in the natural or replacement cycle, and their relevance in the development of a pregnancy or the implications for clinical practice. Methods. Multicenter prospective observational cohort study. Based on our sample size calculation, the study group will consist of 206 women (exposed or "compaction" group: 103 women with a decrease of ≥ 5% in endometrial thickness between the estrogenic phase and the day of embryo transfer; non-exposed "non-compaction" group: 103 women with similar or greater endometrial thickness between these time points). The main objective of this study is to compare the ongoing pregnancy rates in natural cycles for euploid embryo transfer in patients who present endometrial compaction at the time of transfer versus those who with a stable or greater endometrial thickness with respect to the estrogenic phase. The estimated duration of the study is 30 months. Inclusion criteria are: 18 to 50 years of age, with primary or secondary infertility, subjected to endometrial preparation in a modified natural cycle for transfer of a genetically euploid blastocyst, from their own oocyte or oocyte donation, with a normal uterine cavity. Exclusion criteria are: uterine or endometrial disease (e.g., multiple myomatosis, severe adenomyosis, Asherman syndrome, refractory endometrium), conditions that prevent correct ultrasound assessment (tilted uterus), or a PAGE \* Arabic \* MERGEFORMAT This is a provisional file, not the final typeset article history of recurrent implantation failure or repeated miscarriages. Discussion: The findings from this study will provide valuable insights into the potential influence of the "endometrial compaction" phenomenon on reproductive outcomes during natural cycle endometrial preparation. By examining this aspect, we aim to contribute to a better understanding of the factors that may impact successful outcomes in fertility treatments.